Investigation in SrTiO3-CaTiO3-PbTiO3 ternary thin films by dielectric proprieties and Raman spectroscopy - Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Pontes, Fenelon Martinho Lima [UNESP]; Pereira-da-Silva, Marcelo A.; Silva, José Humberto Dias da [UNESP]; Chiquito, A. J.; Pizani, P. S. (Springer, 2010)
Dielectric and Raman scattering experiments were performed on polycrystalline Pb1-x-yCaxSryTiO3 thin films as a function of temperature. Temperature-dependent dielectric measurements revealed a decreasing ferroelectric-to-paraelectric phase transition temperature and peak dielectric permittivity showed a broad phase transition near room temperature with increasing levels of CaO12 and SrO12 clusters. Therefore, for higher levels of substitution, the possible random position of the CaO12 and SrO12 clusters leads to a diffuse state. At 100 kHz, the ferroelectric-to-paraelectric phase transition temperatures were 633, 495 and 206 K for PCST90 (Pb0.90Ca0.05Sr0.05TiO3), PCST70 (Pb0.70Ca0.15Sr0.15TiO3) and PCST30 (Pb0.30Ca0.35Sr0.35TiO3) thin films, respectively. The evolution of the Raman spectra was also studied as a function of temperature. The temperature dependence of the E(1TO) soft mode frequencies was used to characterize the phase transition. Raman peaks were observed above the ferroelectric-to-paraelectric phase transition temperature, although all optical modes should be inactive in Raman scattering. The origin of these modes was interpreted as a breakdown of the local cubic symmetry by the random distribution of CaO12 and SrO12 clusters.
Keywords: Thin films; Phase transition; Ferroelectric; Raman spectroscopy